Method of forming multilayer coating film

By applying water-based primer, water-based paint, effect pigment dispersant and varnish on the plastic molded products in sequence, and heating and curing at a specific temperature, the problem of insufficient appearance and gloss of the finished product in the prior art is solved, and excellent surface finish and finished product appearance are achieved.

CN119857633APending Publication Date: 2025-04-22KANSAI PAINT CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411455151.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-19
Filing Date
2024-10-18
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, when forming a multi-layer coating film, it is difficult to achieve excellent finished product appearance and gloss on plastic molded products, and the surface finish of the cured coating film under low temperature baking conditions is insufficient.

Method used

One method is adopted to apply the aqueous primer, the aqueous base paint, the effect pigment dispersant and the varnish in sequence and heated in a temperature range of 110°C to 130°C to cure the coating film. The aqueous base paint contains hydroxyl-containing acrylic resin particles having a core-shell structure, and the effect pigment dispersant has a solid content of 2% to 6%.

Benefits of technology

A multi-layer coating film with excellent finished appearance and gloss on plastic molded products is achieved, and a good surface finish is maintained under low temperature baking conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005090253680000261
    Figure BDA0005090253680000261
  • Figure BDA0005090253680000271
    Figure BDA0005090253680000271
  • Figure BDA0005090253680000291
    Figure BDA0005090253680000291
Patent Text Reader

Abstract

An object of the present invention is to provide a method for forming a multilayer coating film capable of providing a multilayer coating film having an excellent finished appearance and gloss. The aqueous base paint (X) comprises hydroxyl group-containing acrylic resin particles (X1) having a core-shell structure, wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g; hydroxyl group-containing acrylic resin particles (X2) having a core-shell structure, wherein the acid value of the shell is 110 mg KOH / g to 120 mg KOH / g; and an associative thickener (X3), in which the ratio of the hydroxyl group-containing acrylic resin particles (X1) to the hydroxyl group-containing acrylic resin particles (X2) contained in the aqueous base paint is such that the mass ratio (X1 / X2) of the hydroxyl group-containing acrylic resin particles (X1) to the hydroxyl group-containing acrylic resin particles (X2) is 70 / 30 to 30 / 70. The effect pigment dispersant (Y) contains a sheet-like aluminum pigment (Y1), a cellulose-based rheology control agent (Y2), a surface conditioning agent (Y3), and water, and has a solid content of 2 mass% to 6 mass%. An effect coating film formed using the effect pigment dispersant (Y) has a cured film thickness of 0.5 [mu] m to 1.5 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for forming a multi-layer coating film. Background Art

[0002] Generally, the coating film formed by applying paint to various substrates is required not only to protect the substrates but also to give them an appearance design (aesthetics). In particular, the topcoat paint applied to the exterior panels and bumpers of automobiles is required to be able to form a topcoat film with excellent texture and complex design.

[0003] For example, by using an effect base paint (comprising an effect paint for imparting excellent gloss and a clear varnish) as a top coat, a multilayer coating film having a metallic coating color is formed, which is recently commonly used for top coat films to achieve high-quality designs. The high-grade effect coating film has excellent gloss, and in the coating film, the effect pigment is relatively uniformly present with almost no metallic spots.

[0004] The effect pigments used are usually aluminum pigments with metallic luster. Multilayer coating films with metallic coating colors are usually formed by applying a base paint, an effect base paint containing effect pigments, and a clear coat to a substrate in sequence using a wet-on-wet process, and then curing the resulting uncured coating film with a separate baking treatment.

[0005] For example, Patent Document (PTL) 1 discloses a method for forming a coating film having a metallic luster, the method comprising: sequentially applying a first base metallic paint, a second base effect paint, and a clear coat, and then baking to cure the resulting coating film, wherein the first base metallic paint comprises an aluminum pigment (A) having an average particle size D50 of 13 μm to 40 μm and an average thickness of 0.4 μm to 2.5 μm and an aluminum pigment (B) having an average particle size D50 of 4 μm to 30 μm and an average thickness of 0.02 μm to less than 0.4 μm, wherein the mass ratio (A / B) of the aluminum pigments (A) and (B) based on solid content is 90 / 10 to 10 / 90, and the total mass (A+B) of the aluminum pigments (A) and (B) based on solid content is 5 to 50 parts by mass relative to 100 parts by mass of the resin solid content, and the second base effect paint comprises a fine flake pigment or comprises a fine flake pigment and an aluminum pigment (C). Based on this method, PTL 1 discloses providing a method for forming a coating film having excellent hiding power of an undercoat layer, and excellent brilliance with a flower color and metallic luster, and three-dimensional brilliance.

[0006] However, in the method disclosed in PTL 1, the coating film formed from the second base effect paint has a relatively large film thickness, and the metallic luster is insufficient.

[0007] Patent Document (PTL) 2 discloses a method for forming a multilayer coating film, comprising the following steps (1) to (5):

[0008] (1) applying a colored paint (W) to a substrate and heating to form a colored coating film;

[0009] (2) applying a base paint (X) onto the colored coating film formed in step (1) to form a base coating film;

[0010] (3) applying the effect pigment dispersant (Y) onto the base coating film formed in step (2) to form an effect coating film;

[0011] (4) applying a clear coating (Z) onto the effect coating formed in step (3) to form a clear coating; and

[0012] (5) heating the uncured base coating film, the uncured effect coating film, and the uncured clear coating film formed in steps (2) to (4) to cure the three coating films simultaneously,

[0013] The effect pigment dispersant (Y) comprises water, a surface conditioner (A), a flake effect pigment (B), and a rheology control agent (C), and has a solid content of 0.5 to 10 mass%. PTL 2 discloses that the method can prepare a multilayer coating film exhibiting excellent metallic luster.

[0014] In the method of PTL 2, excellent metallic gloss can be obtained. However, since the effect pigment dispersant (Y) has a low solid content, sagging may occur.

[0015] Especially in the field of automotive coatings, the surface finish of the formed coating film has a significant impact on the commercial quality of the product. Therefore, it is necessary to develop a coating film forming method that can form a multilayer coating film with excellent surface finish and high-quality design.

[0016] Furthermore, unlike the exterior panels, the bumper, which is made of molded plastic, needs to be baked at a relatively low temperature to cure the coating film.

[0017] Reference List

[0018] Patent Literature

[0019] PTL 1: JP2008-237939A

[0020] PTL 2: WO2018 / 092874 Summary of the invention

[0021] Technical issues

[0022] An object of the present invention is to provide a method for forming a multi-layer coating film, which method can provide a multi-layer coating film having excellent finished appearance and excellent gloss on a plastic molded product.

[0023] Solution

[0024] The present invention includes the subject matter described in the following items.

[0025] Project 1

[0026] A method for forming a multilayer coating film comprises the following steps in sequence:

[0027] Step (1): applying a water-based primer (W) on a plastic molded product to form an uncured primer film;

[0028] Step (2): preheating the uncured primer film;

[0029] Step (3): applying a water-based base paint (X) on the preheated base coating film to form an uncured base coating film;

[0030] Step (4): applying an effect pigment dispersant (Y) on the uncured base coating film to form an uncured effect coating film;

[0031] Step (5): preheating the uncured base coating film and the uncured effect coating film;

[0032] Step (6): applying a clear coating (Z) on the preheated effect coating film to form an uncured clear coating film; and

[0033] Step (7): heating the preheated primer film, the preheated base film, the preheated effect film and the uncured clear film at a temperature ranging from 110° C. to 130° C. to simultaneously cure the films, wherein

[0034] The water-based paint (X) comprises

[0035] Hydroxyl-containing acrylic resin particles (X1) having a core-shell structure, wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g;

[0036] Hydroxyl-containing acrylic resin particles (X2) having a core-shell structure, wherein the acid value of the shell is 110 mg KOH / g to 120 mg KOH / g; and

[0037] Associative thickener (X3);

[0038] The mass ratio (X1 / X2) of the hydroxyl-containing acrylic resin particles (X1) to the hydroxyl-containing acrylic resin particles (X2) contained in the water-based paint is 70 / 30 to 30 / 70;

[0039] The effect pigment dispersant (Y) comprises

[0040] Flake aluminum pigment (Y1),

[0041] Cellulose-based rheology control agent (Y2),

[0042] a surface conditioner (Y3), and

[0043] water, and

[0044] The effect pigment dispersant (Y) has a solid content of 2% by mass to 6% by mass; and

[0045] The effect coating film after curing has a film thickness of 0.5 μm to 1.5 μm.

[0046] Beneficial Effects of the Invention

[0047] The present invention can provide a method for forming a multilayer coating film having excellent finished appearance and excellent gloss on a plastic molded product. DETAILED DESCRIPTION

[0048] The method for forming a multilayer coating of the present invention comprises the following steps in sequence:

[0049] Step (1): applying a water-based primer (W) on a plastic molded product to form an uncured primer film;

[0050] Step (2): preheating the uncured primer film;

[0051] Step (3): applying a water-based base paint (X) on the preheated base coating film to form an uncured base coating film;

[0052] Step (4): applying an effect pigment dispersant (Y) on the uncured base coating film to form an uncured effect coating film;

[0053] Step (5): preheating the uncured base coating film and the uncured effect coating film;

[0054] Step (6): applying a clear coating (Z) on the preheated effect coating film to form an uncured clear coating film; and

[0055] Step (7): heating the preheated primer film, the preheated base film, the preheated effect film and the uncured clear film at a temperature ranging from 110° C. to 130° C. to simultaneously cure the films, wherein

[0056] Wherein, the water-based paint (X) comprises

[0057] Hydroxyl-containing acrylic resin particles (X1) having a core-shell structure, wherein the acid value of the shell is 90 mg KOH / g

[0058] To 100 mg KOH / g;

[0059] Hydroxyl-containing acrylic resin particles (X2) having a core-shell structure, wherein the acid value of the shell is 110 mg KOH / g

[0060] to 120 mg KOH / g; and

[0061] Associative thickener (X3);

[0062] wherein the mass ratio (X1 / X2) of the hydroxyl-containing acrylic resin particles (X1) to the hydroxyl-containing acrylic resin particles (X2) contained in the paint is 70 / 30 to 30 / 70;

[0063] wherein the effect pigment dispersant (Y) comprises a flake aluminum pigment (Y1), a cellulose-based rheology control agent (Y2), a surface conditioner (Y3), and water, and has a solid content of 2% to 6% by mass; and

[0064] The effect coating film after curing has a film thickness of 0.5 μm to 1.5 μm.

[0065] Step (1)

[0066] Step (1) of the present invention is a step of applying a water-based primer (W) on a plastic molded article to form an uncured base coating film.

[0067] Plastic molded products

[0068] Particularly preferred examples of materials for plastic molded articles include, but are not limited to, those obtained by polymerizing at least one C2-C 10 Examples of polyolefins include polyolefins obtained by reacting olefins such as ethylene, propylene, butene and hexene. Other examples include polycarbonate, ABS resin, polyurethane resin and nylon.

[0069] The plastic molded product can be obtained, for example, by molding the above-mentioned materials by injection molding or similar known methods. The plastic molded product can be appropriately subjected to degreasing, water washing, etc. in advance by known methods.

[0070] Water-based primer (W)

[0071] In the present specification, the "water-based primer (W)" is a water-based paint for imparting high adhesion to the paint formed on the plastic molded article.

[0072] The water-based primer (W) used in this step is preferably a water-based paint commonly used in the art, which contains a base resin, a curing agent, an organic solvent and water.

[0073] The base resin and the curing agent can be known compounds commonly used in the art. Examples of the base resin include acrylic resins, polyester resins, polyurethane resins, and olefin resins. Examples of the curing agent include amino resins, polyisocyanate compounds, and blocked polyisocyanate compounds.

[0074] Examples of the organic solvent include hydrocarbons such as aliphatic hydrocarbons (e.g., hexane and heptane), aromatic hydrocarbons (e.g., xylene and toluene), and alicyclic hydrocarbons; esters such as ethyl acetate and butyl acetate; ethers such as ethylene glycol monomethyl ether; alcohols such as ethanol, propanol, and 2-ethylhexanol; ketones such as methyl ethyl ketone and methyl isobutyl ketone; amides; and other solvents. Examples of organic solvents containing aromatic hydrocarbons include Swasol 310 and Swasol 1000 (produced by Cosmo Oil Co., Ltd., Japan).

[0075] The water-based primer (W) used in the method of the present invention may contain, in addition to the above-mentioned components, an ultraviolet absorber, a defoamer, a thickener, a rust preventive, a surface conditioner, a pigment, etc. as required.

[0076] The water-based primer (W) can be applied by using conventional coating methods commonly used in this area. The example of the coating method includes a coating method using a brush or an applicator. Wherein, the coating method of the applicator is preferably used. For example, the applicator is preferably an airless sprayer, an air sprayer or a rotary atomizing applicator, such as a paint box applicator, and a particularly preferred rotary atomizing applicator. The use of the above-mentioned paint and coating method can form an uncured base coating film with excellent coating appearance.

[0077] The base coating film preferably has a film thickness of 5 μm to 20 μm, and particularly preferably 7 μm to 15 μm, based on the cured base coating film.

[0078] Step (2)

[0079] The step (2) of the present invention is a step of preheating the uncured base coating film.

[0080] In this specification, "preheating" refers to the following treatment: heating the object to be coated and the coating formed on its surface under certain temperature conditions for a period of time so that the base resin and curing agent in the coating do not react or cure, or basically do not react or cure, thereby volatilizing the aqueous medium and / or other volatile substances in the coating.

[0081] The preheating temperature is preferably 40° C. to 80° C., more preferably 50° C. to 70° C. The preheating time is preferably 1 to 5 minutes.

[0082] Step (3)

[0083] Step (3) of the present invention is a step of applying a water-based base paint (X) on the preheated base coating film to form an uncured base coating film.

[0084] Water-based paint(X)

[0085] In the present specification, the "water-based paint (X)" refers to a water-based paint used to improve the appearance of a finished product by hiding the underlying primer.

[0086] The water-based paint (X) comprises: hydroxyl-containing acrylic resin particles (X1) having a core-shell structure, wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g; hydroxyl-containing acrylic resin particles (X2) having a core-shell structure, wherein the acid value of the shell is 110 mg KOH / g to 120 mg KOH / g; and an associative thickener (X3), wherein the mass ratio (X1 / X2) of the hydroxyl-containing acrylic resin particles (X1) to the hydroxyl-containing acrylic resin particles (X2) in the water-based paint is in the range of 70 / 30 to 30 / 70.

[0087] Considering the finished appearance of the obtained coating film, the mass ratio (X1 / X2) of the hydroxyl-containing acrylic resin particles (X1) to the hydroxyl-containing acrylic resin particles (X2) is preferably 65 / 35 to 35 / 65, more preferably 60 / 40 to 40 / 60.

[0088] In the present invention, the "shell part" of the "hydroxyl-containing acrylic resin particles having a core-shell structure" refers to a polymer layer existing as the outermost layer of the resin particles, the "core part" refers to a polymer layer in the resin particles except the shell part, and the "core-shell structure" refers to a structure having the core part and the shell part. The core-shell structure generally refers to a layer structure in which the core part is completely covered by the shell part. However, depending on, for example, the mass ratio of the core part and the shell part, the amount of monomers in the shell part may not be sufficient to form such a layer structure. In this case, the core-shell structure is not necessarily a complete layer structure as described above. The core-shell structure can be a structure in which a portion of the core is covered by the shell.

[0089] The hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g) are acrylic resin particles comprising a core portion, the core portion being a copolymer (I) comprising a polymerizable unsaturated monomer as a copolymer component, and a shell portion being a copolymer (II) comprising a polymerizable unsaturated monomer as a copolymer component. The acid value of the shell portion can be calculated from the monomer composition.

[0090] The polymerizable unsaturated monomer used may be a suitable combination of a hydroxyl-containing polymerizable unsaturated monomer, an acid group-containing polymerizable unsaturated monomer, and another polymerizable unsaturated monomer copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer and the acid group-containing polymerizable unsaturated monomer.

[0091] The hydroxyl-containing polymerizable unsaturated monomer is a compound containing one or more hydroxyl groups and one or more polymerizable unsaturated bonds per molecule. Examples of the hydroxyl-containing polymerizable unsaturated monomer include monoesterification products of (meth)acrylic acid and diols having 2 to 8 carbon atoms (e.g., 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate); ε-caprolactone-modified products of such monoesterification products of (meth)acrylic acid and diols having 2 to 8 carbon atoms; N-hydroxymethyl (meth)acrylamide; allyl alcohol; and (meth)acrylates having a hydroxyl-terminated polyoxyethylene chain, however, in the present invention, the monomer corresponding to (xiv) the polymerizable unsaturated monomer having a UV absorbing functional group described later is to be excluded from the above-mentioned hydroxyl-containing polymerizable unsaturated monomers and should be included in other polymerizable unsaturated monomers copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer. Such monomers may be used alone or in combination of two or more.

[0092] The acid group-containing polymerizable unsaturated monomer refers to a compound having one or more acid groups and one or more polymerizable unsaturated bonds per molecule. Examples of the acid group include a carboxylic acid group, a phosphoric acid group, and a sulfuric acid group, preferably a carboxylic acid group.

[0093] Examples of the compound having one or more carboxylic acid groups and one or more polymerizable unsaturated bonds include acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic acid, and maleic anhydride.

[0094] Examples of the compound having one or more phosphoric acid groups and one or more polymerizable unsaturated bonds include acid phosphooxyethyl (meth) acrylate, acid phosphooxypropyl (meth) acrylate, acid phosphooxy poly (oxyethylene) glycol (meth) acrylate, and acid phosphooxy poly (oxypropylene) glycol (meth) acrylate.

[0095] Examples of the compound having one or more sulfate groups and one or more polymerizable unsaturated bonds include 2-acrylamido-2-methylpropanesulfonic acid, 2-sulfoethyl (meth)acrylate, allylsulfonic acid, 4-styrenesulfonic acid, and the like; and sodium salts and ammonium salts of these sulfonic acids.

[0096] Examples of other polymerizable unsaturated monomers copolymerizable with the hydroxyl group-containing polymerizable unsaturated monomer and the acid group-containing polymerizable unsaturated monomer include the following monomers (i) to (xvii). Such other polymerizable unsaturated monomers may be used alone or in combination of two or more.

[0097] (i) Alkyl or cycloalkyl (meth)acrylates: Examples include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, tridecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, and tricyclodecyl (meth)acrylate.

[0098] (ii) Isobornyl group-containing polymerizable unsaturated monomer: Examples include isobornyl (meth)acrylate.

[0099] (iii) Adamantyl group-containing polymerizable unsaturated monomer: Examples include adamantyl (meth)acrylate.

[0100] (iv) Tricyclodecenyl group-containing polymerizable unsaturated monomer: Examples include tricyclodecenyl (meth)acrylate.

[0101] (v) Aromatic ring-containing polymerizable unsaturated monomers: Examples include benzyl (meth)acrylate, styrene, α-methylstyrene, and vinyltoluene.

[0102] (vi) Alkoxysilyl group-containing polymerizable unsaturated monomers: Examples include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-(meth)acryloxypropyltrimethoxysilane, and γ-(meth)acryloxypropyltriethoxysilane.

[0103] (vii) Polymerizable unsaturated monomers having a fluorinated alkyl group: Examples include perfluoroalkyl (meth)acrylates (such as perfluorobutyl ethyl (meth)acrylate and perfluorooctyl ethyl (meth)acrylate), and fluoroolefins.

[0104] (viii) Polymerizable unsaturated monomer having a photopolymerizable functional group: Examples include maleimide.

[0105] (ix) Vinyl compounds: Examples include N-vinyl pyrrolidone, ethylene, butadiene, chloroprene, vinyl propionate, and vinyl acetate.

[0106] (x) Nitrogen-containing polymerizable unsaturated monomers: Examples include (meth)acrylonitrile, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, methylenebis (meth)acrylamide, ethylenebis (meth)acrylamide, and adducts of glycidyl (meth)acrylate and amine compounds.

[0107] (xi) Polymerizable unsaturated monomers having two or more polymerizable unsaturated groups per molecule: Examples include allyl (meth)acrylate, ethylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate.

[0108] (xii) Epoxy-containing polymerizable unsaturated monomers: Examples include glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxycyclohexylethyl (meth)acrylate, 3,4-epoxycyclohexylpropyl (meth)acrylate, and allyl glycidyl ether.

[0109] (xiii) (Meth)acrylates having alkoxy-terminated polyoxyethylene chains.

[0110] (xiv) Polymerizable unsaturated monomers having an ultraviolet absorbing functional group: Examples include 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2-hydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, and 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole.

[0111] (xv) Light-stable polymerizable unsaturated monomers: Examples include 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine, 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloylamino-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloylamino-4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 4-crotonyloxy-2,2,6,6-tetramethylpiperidine, 4-crotonylamino-2,2,6,6-tetramethylpiperidine, and 1-crotonyl-4-crotonyloxy-2,2,6,6-tetramethylpiperidine.

[0112] (xvi) Polymerizable unsaturated monomers having a carbonyl group: Examples include acrolein, diacetone acrylamide, diacetone methacrylamide, acetoacetoxyethyl methacrylate, formylstyrene, and vinyl alkyl ketones having 4 to 7 carbon atoms (e.g., vinyl methyl ketone, vinyl ethyl ketone, and vinyl butyl ketone).

[0113] (xvii) Polymerizable unsaturated monomer having an acid anhydride group: Examples include maleic anhydride, itaconic anhydride, and citraconic anhydride.

[0114] In the present specification, the polymerizable unsaturated group refers to an unsaturated group that can be polymerized radically. Examples of such polymerizable unsaturated groups include a vinyl group and a (meth)acryloyl group.

[0115] In this specification, the term "(meth)acrylate" refers to acrylate or methacrylate. The term "(meth)acrylic acid" refers to acrylic acid or methacrylic acid. The term "(meth)acryloyl" refers to acryloyl or methacryloyl. The term "(meth)acrylamide" refers to acrylamide or methacrylamide.

[0116] In a typical embodiment, in order to prepare the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g), an emulsion for the core copolymer (I) is first prepared by emulsion polymerization of a polymerizable unsaturated monomer mixture.

[0117] The emulsion polymerization for preparing the emulsion for the core copolymer (I) can be carried out according to a known method. For example, the emulsion can be prepared by emulsion polymerization of a monomer mixture using a polymerization initiator in the presence of an emulsifier.

[0118] Examples of the emulsifier that can be preferably used include anionic surfactants and nonionic surfactants.

[0119] Examples of anionic emulsifiers include sodium and ammonium salts of alkylsulfonic acids, alkylbenzenesulfonic acids, and alkylphosphoric acids. Examples of nonionic emulsifiers include polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyethylene phenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, sorbitan monolaurate, sorbitan monostearate, sorbitan trioleate, and polyoxyethylene sorbitan monolaurate.

[0120] Other examples of usable anionic emulsifiers include polyoxyalkylene group-containing anionic emulsifiers having an anionic group and a polyoxyalkylene group (eg, a polyoxyethylene group or a polyoxypropylene group) per molecule; and reactive anionic emulsifiers having an anionic group and a radically polymerizable unsaturated group per molecule.

[0121] Examples of the reactive anionic surfactant include sodium salts of sulfonic acid compounds having a radically polymerizable unsaturated group such as an allyl group, a methallyl group, a (meth)acryloyl group, a propenyl group, or a butenyl group; and ammonium salts of such sulfonic acid compounds.

[0122] The emulsifier is preferably used in an amount of about 0.1 to 15 mass %, more preferably about 0.5 to 10 mass %, even more preferably about 1 to 5 mass %, based on the total amount of monomers used to prepare the core copolymer.

[0123] Examples of the polymerization initiator include organic peroxides such as benzoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, cumene hydroperoxide, tert-butyl peroxide, tert-butyl peroxide laurate, tert-butyl carbonate peroxide isopropyl, tert-butyl peroxyacetate, and dicumyl hydroperoxide; azo compounds such as azobisisobutyronitrile, azobis(2,4-dimethylvaleronitrile), azobis(2-methylpropionitrile), azobis(2-methylbutyronitrile), 4,4'-azobis(4-cyanobutyric acid), dimethylazobis(2-methylpropionate), azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], and azobis{2-methyl-N-[2-(1-hydroxybutyl)]-propionamide}; and persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate. Such polymerization initiators may be used alone or in combination of two or more. Redox initiators prepared by combining a polymerization initiator, such as those described above, with a reducing agent, such as a sugar, sodium formaldehyde sulfoxylate, or an iron complex, may also be used.

[0124] Typically, the amount of the polymerization initiator is preferably about 0.1% to 5% by mass, particularly preferably about 0.2% to 3% by mass, based on the total amount of monomers used to prepare the core copolymer. The method of adding the polymerization initiator is not particularly limited and can be appropriately selected according to, for example, the type and amount of the polymerization initiator used. For example, the polymerization initiator can be pre-incorporated into the monomer mixture or the aqueous medium, or can be added all at once or added dropwise during polymerization.

[0125] By using a polymerizable unsaturated monomer having two or more polymerizable unsaturated groups per molecule as the polymerizable unsaturated monomer, a crosslinked structure can be imparted to the copolymer. When using a polymerizable unsaturated monomer having two or more polymerizable unsaturated groups per molecule, the proportion of the polymerizable unsaturated monomer used can be appropriately determined according to the crosslinking degree of the copolymer. Typically, based on the total amount of the polymerizable unsaturated monomer used to prepare the core copolymer, the proportion is preferably from about 0.1% to 30% by mass, particularly preferably from about 0.5% to 10% by mass, and more particularly preferably from about 1% to 7% by mass.

[0126] The hydroxyl group-containing acrylic resin particles (X1) having a core-shell structure, wherein the acid value of the shell is 90 to 100 mg KOH / g, can be obtained by further forming a shell copolymer (II).

[0127] If desired, the monomer mixture for forming the shell copolymer (II) may suitably contain a polymerization initiator (such as those described above), a chain transfer agent, a reducing agent, an emulsifier, and other components. The monomer mixture may be added dropwise as is, but is preferably dispersed in an aqueous medium and then added dropwise as a monomer emulsion. In this case, the particle size of the monomer emulsion is not particularly limited.

[0128] The method for polymerizing the monomer mixture to form the shell copolymer (II) can be performed, for example, by adding the monomer mixture or its emulsion all at once or dropwise and heating the mixture to an appropriate temperature while stirring.

[0129] In view of the final appearance of the obtained coating film, the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 to 100 mg KOH / g) preferably have a hydroxyl value of 1 to 50 mg KOH / g, more preferably 2 to 30 mg KOH / g, further preferably 3 to 20 mg KOH / g.

[0130] In view of the water resistance of the resulting coating film, etc., the core portion of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g) preferably has a hydroxyl value of 20 mg KOH / g or less, more preferably 15 mg KOH / g or less, further preferably 10 mg KOH / g or less.

[0131] In view of the water resistance of the resulting coating film and the like, the shell portion of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 to 100 mg KOH / g) preferably has a hydroxyl value of 20 to 80 mg KOH / g, more preferably 25 to 70 mg KOH / g or less, further preferably 30 to 60 mg KOH / g.

[0132] In view of the storage stability of the paint, the water resistance of the resulting coating film, etc., the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g) preferably have an acid value of 5 mg KOH / g to 50 mg KOH / g, more preferably 10 mg KOH / g to 40 mg KOH / g, and further preferably 15 mg KOH / g to 30 mg KOH / g.

[0133] In view of the production stability, storage stability, etc. of the paint, the core part of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 to 100 mg KOH / g) preferably has an acid value of 20 mg KOH / g or less, more preferably 15 mg KOH / g or less, further preferably 10 mg KOH / g or less.

[0134] In view of the water resistance of the obtained coating film, the hydroxyl group-containing acrylic resin particles (X1) having a core-shell structure (shell acid value of 90 to 100 mg KOH / g) preferably have a glass transition temperature of 20°C or higher, more preferably 30°C or higher, further preferably 30°C to 60°C.

[0135] The core portion of the hydroxyl group-containing acrylic resin particles (X1) having a core-shell structure (wherein the shell has an acid value of 90 to 100 mg KOH / g) preferably has a glass transition temperature of 20°C or higher, more preferably 30°C or higher, further preferably 30°C to 60°C.

[0136] The hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g) preferably include a shell portion having a glass transition temperature of 0° C. or higher, more preferably 5° C. or higher, further preferably 5° C. to 30° C., in view of coating film formability and the like.

[0137] In this specification, the glass transition temperature Tg refers to the value calculated according to the following formula:

[0138] 1 / Tg(K)=W1 / T1+W2 / T2+···Wn / Tn

[0139] Tg(℃)=Tg(K)-273

[0140] Wherein, W1, W2···Wn are the mass fractions of each monomer; T1, T2···Tn are the glass transition temperatures Tg (K) of the homopolymers of each monomer.

[0141] The glass transition temperature of the homopolymer of each monomer is a value shown in the Polymer Handbook, 4th edition, edited by J. Brandrup, EH Immergut and EA Grulke in 1999. When the glass transition temperature of a monomer is not shown in the handbook, a homopolymer of the monomer having a weight average molecular weight of about 50,000 is synthesized, and the glass transition temperature of the homopolymer measured by differential scanning calorimetry is used as the glass transition temperature of the monomer.

[0142] The content of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g) in the water-based paint (X) is preferably 2% to 70% by mass, more preferably 5% to 50% by mass, and further preferably 10% to 40% by mass, based on the resin solid content of the water-based paint (X).

[0143] The hydroxyl-containing acrylic resin particles (X2) having a core-shell structure (wherein the acid value of the shell is 110 to 120 mg KOH / g) can be prepared in the same manner as the method for preparing the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 to 100 mg KOH / g).

[0144] In view of the final appearance of the resulting coating film and the like, the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure wherein the acid value of the shell is 110 to 120 mg KOH / g preferably have a hydroxyl value of 1 to 50 mg KOH / g, more preferably 2 to 30 mg KOH / g, further preferably 3 to 20 mg KOH / g.

[0145] In view of the water resistance of the resulting coating film, etc., the core portion of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure (wherein the acid value of the shell is 110 mg KOH / g to 120 mg KOH / g) preferably has a hydroxyl value of 20 mg KOH / g or less, more preferably 15 mg KOH / g or less, further preferably 10 mg KOH / g or less.

[0146] In view of the water resistance of the resulting coating film and the like, the shell of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure (wherein the shell has an acid value of 110 to 120 mg KOH / g) preferably has a hydroxyl value of 20 to 80 mg KOH / g, more preferably 25 to 70 mg KOH / g or less, further preferably 30 to 60 mg KOH / g.

[0147] In view of the storage stability of the paint, the water resistance of the resulting coating film, etc., the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure (wherein the acid value of the shell is 110 mg KOH / g to 120 mg KOH / g) preferably have an acid value of 5 mg KOH / g to 50 mg KOH / g, more preferably 10 mg KOH / g to 40 mg KOH / g, and further preferably 15 mg KOH / g to 30 mg KOH / g.

[0148] In view of the production stability, storage stability, etc. of the paint, the core part of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure (wherein the acid value of the shell is 110 mg KOH / g to 120 mg KOH / g) preferably has an acid value of 20 mg KOH / g or less, more preferably 15 mg KOH / g or less, further preferably 10 mg KOH / g or less.

[0149] The hydroxyl-containing acrylic resin particles (X2) having a core-shell structure (wherein the acid value of the shell is 110 to 120 mg KOH / g) preferably have a glass transition temperature of 10°C or higher, more preferably 20°C or higher, further preferably 20°C to 50°C, in view of the water resistance and the like of the resulting coating film.

[0150] The core portion of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure (wherein the acid value of the shell is 110 to 120 mg KOH / g) preferably has a glass transition temperature of 10°C or higher, more preferably 20°C or higher, and further preferably 20°C to 50°C, in view of the water resistance of the resulting coating film, the formability of the coating film, and the like.

[0151] In view of film formation of the paint, etc., the shell portion of the hydroxyl group-containing acrylic resin particles (X2) having a core-shell structure (wherein the acid value of the shell is 110 mg KOH / g to 120 mg KOH / g) preferably has a glass transition temperature of 20°C or higher, more preferably 30°C or higher, further 30°C to 60°C.

[0152] The content of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure (wherein the acid value of the shell is 110 mg KOH / g to 120 mg KOH / g) in the water-based paint (X) is preferably 2% by mass to 70% by mass, more preferably 5% by mass to 50% by mass, and further preferably 10% by mass to 40% by mass, based on the resin solid content of the water-based paint (X).

[0153] The associative thickener (X3) is a thickener having a hydrophilic part and a hydrophobic part in the molecule and having an effect of effectively improving the viscosity in an aqueous medium by adsorbing the hydrophobic part on the surface of the pigment or resin particles in the paint or by association between the hydrophobic parts.

[0154] The associative thickener (X3) may be a commercially available product. Examples of commercially available products that can be used include "UH-420", "UH-450", "UH-462", "UH-472", "UH-540", "UH-752", "UH-756VF" and "UH-814N" produced by Adeka Group; "PRIMAL RM-8W", "PRIMAL RM-825", "PRIMAL 2020NPR", "PRIMAL RM-12W" and "PRIMAL SCN-275" produced by Rohm and Haas; and "SN Thickener 612", "SN Thickener 621N", "SN Thickener 625N", "SN Thickener 627N" and "SN Thickener 660T" produced by San Nopco.

[0155] Based on the resin solid content of the water-based paint (X) being 100 parts by mass, the content of the associative thickener (X3) in the water-based paint (X) is preferably 0.1 parts by mass to 5 parts by mass, more preferably 0.2 parts by mass to 4 parts by mass, and further preferably 0.3 parts by mass to 3 parts by mass.

[0156] If necessary, the water-based paint (X) may further contain: resins other than the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2), curing agents, pigments, organic solvents, curing catalysts, dispersants, anti-settling agents, defoaming agents, thickeners other than the associative thickener (X3), ultraviolet absorbers, light stabilizers, surface regulators, etc.

[0157] Examples of the resin other than the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2) include acrylic resins other than the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2), polyester resins, and polyurethane resins.

[0158] Examples of the curing agent include amino resins, polyisocyanate compounds, and blocked polyisocyanate compounds.

[0159] Examples of the pigment include color pigments, extender pigments, and gloss pigments. These pigments may be used alone or in combination of two or more.

[0160] When the water-based coating paint (X) contains a pigment as described above, the amount of the pigment is preferably 1 to 50 parts by mass, more preferably 2 to 40 parts by mass, and further preferably 3 to 30 parts by mass, based on 100 parts by mass of the resin solid content of the water-based coating paint (X).

[0161] Examples of the colored pigment include titanium oxide, zinc oxide, carbon black, molybdenum red, Prussian blue, cobalt blue, azo pigments, phthalocyanine pigments, quinacridone pigments, isoindoline pigments, anthracene pigments, perylene pigments, dioxazine pigments, and diketopyrrolopyrrole pigments.

[0162] When the water-based paint (X) contains a colored pigment as described above, the content of the colored pigment is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and further preferably 1 to 10 parts by mass, based on 100 parts by mass of the total resin solid content of the water-based paint (X).

[0163] Examples of the extender pigment include barium sulfate, talc, clay, kaolin, barium carbonate, calcium carbonate, silica, and alumina white.

[0164] When the water-based paint (X) contains an extender pigment as described above, the amount of the extender pigment is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and further preferably 1 to 10 parts by mass, based on 100 parts by mass of the resin solid content of the water-based paint (X).

[0165] Examples of the effect pigment include aluminum (including vapor-deposited aluminum), copper, zinc, brass, nickel, glass flakes, aluminum oxide, mica, aluminum oxide coated with titanium oxide and / or iron oxide, and mica coated with titanium oxide and / or iron oxide. Among them, aluminum pigments are preferably used. Examples of aluminum pigments include non-leafing aluminum pigments and leafing aluminum pigments, either of which can be used.

[0166] The effect pigments are preferably in platelet form. Suitable effect pigments preferably have a longitudinal dimension of 1 μm to 100 μm, particularly preferably 5 μm to 40 μm, and a thickness of 0.001 μm to 5 μm, particularly preferably 0.01 μm to 2 μm.

[0167] When the water-based paint (X) contains the effect pigment as described above, the amount of the effect pigment is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and further preferably 1 to 10 parts by mass, based on 100 parts by mass of the resin solid content of the water-based paint (X).

[0168] Examples of the organic solvent include ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester solvents such as ethyl acetate, butyl acetate, methyl benzoate, ethyl ethoxypropionate, ethyl propionate, and methyl propionate; alcohol solvents such as isopropanol, n-butanol, isobutanol, and 2-ethylhexanol; ether solvents such as tetrahydrofuran, dioxane, and dimethoxyethane; glycol ether solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, and the like.

[0169] Examples of thickeners other than the associative thickener (X3) include alkali swelling thickeners.

[0170] Before use, if necessary, the water-based paint (X) may be diluted to an appropriate viscosity by adding water and / or an organic solvent, etc., and then applied. The appropriate viscosity varies depending on the composition of the paint. For example, it is preferred to appropriately adjust the viscosity using water and / or an organic solvent to achieve a viscosity within the range of 2000 mPa·s to 5000 mPa·s measured at 20°C and 6 rpm using a Brookfield viscometer.

[0171] The method for applying the water-based paint (X) can be a conventional coating method commonly used in the art. Examples of the coating method include a coating method using a brush or an applicator. Among them, the coating method using an applicator is preferred. Preferred examples of the applicator include an airless sprayer, an air sprayer, and a rotary atomizing electrostatic coater, such as a paint box coater. A rotary atomizing electrostatic coater is particularly preferred. By using the above-mentioned coating material and coating method, an uncured base coating film with a good coating appearance can be obtained.

[0172] The cured film thickness of the base coating film is preferably 5 μm to 15 μm, particularly preferably 7 μm to 12 μm.

[0173] Step (4)

[0174] Step (4) of the present invention is a step of coating the effect pigment dispersant (Y) on the uncured base coating film to form an uncured effect coating film.

[0175] Effect Pigment Dispersant (Y)

[0176] In the present specification, "effect pigment dispersant (Y)" is a water-based paint containing a flake aluminum pigment (Y1), a cellulose-based rheology control agent (Y2), a surface conditioner (Y3), and water, and having a solid content of 2 to 6 mass%. The effect pigment dispersant (Y) is used to impart gloss.

[0177] Examples of the flake aluminum pigment (Y1) include aluminum flake pigments and vapor-deposited aluminum flake pigments.

[0178] The aluminum flake pigment is usually produced by crushing and grinding aluminum in a ball mill or attritor using a grinding aid in the presence of a grinding medium. The grinding aid used in the step of producing the aluminum flake pigment includes higher fatty acids, such as oleic acid, stearic acid, isostearic acid, lauric acid, palmitic acid, and myristic acid, as well as aliphatic amines, aliphatic amides, and aliphatic alcohols. The grinding liquid medium used includes aliphatic hydrocarbons, such as mineral spirits.

[0179] The aluminum flake pigment is broadly divided into a leafing aluminum flake pigment and a non-leafing aluminum flake pigment according to the type of grinding aid. In the gloss pigment dispersant (Y), it is preferred to use a non-leafing flaky aluminum pigment to obtain a multilayer coating film with excellent gloss. The non-leafing flaky aluminum pigment used may be those whose surface is not specially treated, whose surface is coated with a resin, whose surface is treated with silicon dioxide, or whose surface is treated with phosphoric acid, molybdic acid or a silane coupling agent. The non-leafing flaky aluminum pigment used may be a non-leafing flaky aluminum pigment subjected to one or more such surface treatments.

[0180] The vapor-deposited aluminum flake pigment is obtained by vapor-depositing an aluminum film on a substrate, removing the substrate, and then grinding the vapor-deposited aluminum film. Examples of the substrate include thin films.

[0181] Examples of commercially available products that can be used as vapor-deposited aluminum flake pigments include “METALURE” series (trade name, produced by Eckart), “Hydroshine WS” series (trade name, produced by Eckart), “Demet” series (trade name, produced by Schlenk), and “Metasheen” series (trade name, produced by BASF).

[0182] The content of the flaky aluminum pigment (Y1) is preferably 30 parts by mass to 80 parts by mass, more preferably 40 parts by mass to 70 parts by mass, per 100 parts by mass of the solid content of the effect pigment dispersant (Y).

[0183] Examples of the cellulose-based rheology control agent (Y2) include carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, cellulose nanofibers, and cellulose nanocrystals. Among them, cellulose nanofibers are preferably used.

[0184] The cellulose nanofibers preferably have a number average fiber diameter of 2 nm to 500 nm, more preferably 2 nm to 250 nm, further preferably 2 nm to 150 nm, and preferably have a number average fiber length of 0.1 μm to 20 μm, more preferably 0.1 μm to 15 μm, further preferably 0.1 μm to 10 μm.

[0185] The number average fiber diameter and the number average fiber length are measured and calculated from, for example, images obtained by dispersing a cellulose nanofiber sample diluted with water, casting the sample on a grid coated with a hydrophilic-treated carbon film, and observing the sample with a transmission electron microscope (TEM).

[0186] The cellulose nanofibers used may be obtained by defibration of a cellulose material and stabilization thereof in water. The cellulose material used herein refers to various forms of raw materials mainly composed of cellulose. Specific examples include pulp (e.g., pulp from herbaceous plants such as wood pulp, jute, abaca, and kenaf); natural cellulose, such as cellulose produced by microorganisms; regenerated cellulose obtained by dissolving cellulose in a solvent such as a cuprammonium solution or a morpholine derivative and spinning the dissolved cellulose; and fine cellulose obtained by subjecting a cellulose material to mechanical treatment such as hydrolysis, alkaline hydrolysis, enzymatic decomposition, air blast treatment, or vibration ball milling to depolymerize cellulose.

[0187] The cellulose nanofibers used can be anion-modified cellulose nanofibers. Examples of anion-modified cellulose nanofibers include carboxylated cellulose nanofibers, carboxymethylated cellulose nanofibers, cellulose nanofibers containing sulfuric acid groups, and cellulose nanofibers containing phosphoric acid groups. The anion-modified cellulose nanofibers can, for example, be obtained by introducing functional groups such as carboxyl and carboxymethyl groups into a cellulosic material by a known method, washing the obtained modified cellulose to prepare a dispersant for the modified cellulose, and defiberizing the dispersant. The carboxylated cellulose is also referred to as "oxidized cellulose".

[0188] The oxidized cellulose can be obtained, for example, by oxidizing a cellulose material in water using an oxidizing agent in the presence of a compound selected from the group consisting of N-oxyl compounds, bromides, iodides, and mixtures thereof.

[0189] Examples of commercial products of cellulose nanofibers include Rheocrysta (registered trademark) produced by DKS Co., Ltd. and Aurovisc (registered trademark) produced by Oji Holdings Corporation.

[0190] The content of the cellulose-based rheology control agent (Y2) is preferably 5 parts by mass to 30 parts by mass, more preferably 7 parts by mass to 20 parts by mass, based on 100 parts by mass of the solid content of the effect pigment dispersant (Y).

[0191] Examples of the surface conditioner (Y3) include surface conditioners such as silicone-based surface conditioners, acrylic surface conditioners, vinyl-based surface conditioners, fluorine-based surface conditioners, and acetylene glycol-based surface conditioners. Among them, acetylene glycol-based surface conditioners are preferred.

[0192] Examples of commercial products of the surface conditioner (Y3) include Dynol series, Surfynol series, and Tego series (produced by Evonik Industries AG), BYK series (produced by BYK-Chemie), Glanol series and Polyflow series (produced by Kyoeisha Chemical Co., Ltd.), and Disparlon series (produced by Kusumoto Chemicals, Ltd.).

[0193] The content of the surface conditioner (Y3) is preferably 2 parts by mass to 15 parts by mass, more preferably 4 parts by mass to 10 parts by mass, relative to 100 parts by mass of the solid content of the effect pigment dispersant (Y).

[0194] The effect pigment dispersant (Y) has a solid content of 2 to 6 mass %. When the solid content is 2 to 6 mass %, a multilayer coating film having excellent gloss can be obtained.

[0195] If necessary, the effect pigment dispersant (Y) may further appropriately contain a resin, a curing agent, an effect pigment other than the flake aluminum pigment (Y1), a color pigment, an extender pigment, an organic solvent, a rheology control agent other than the cellulose-based rheology control agent (Y2), an anti-settling agent, a defoaming agent, an ultraviolet absorber, a light stabilizer, and the like.

[0196] Examples of the resin include acrylic resins, polyester resins, and polyurethane resins.

[0197] Examples of the curing agent include amino resins, polyisocyanate compounds, and blocked polyisocyanate compounds.

[0198] Examples of the colored pigment include titanium oxide, zinc oxide, carbon black, molybdenum red, Prussian blue, cobalt blue, azo pigments, phthalocyanine pigments, quinacridone pigments, isoindoline pigments, anthracene pigments, perylene pigments, dioxazine pigments, and diketopyrrolopyrrole pigments.

[0199] When the effect pigment dispersant (Y) contains a colored pigment as described above, the amount of the colored pigment used is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and further preferably 0.3 to 3 parts by mass, relative to 100 parts by mass of the solid content of the effect pigment dispersant (Y).

[0200] Examples of the extender pigment include barium sulfate, talc, clay, kaolin, barium carbonate, calcium carbonate, silica, and alumina white.

[0201] When the effect pigment dispersant (Y) contains an extender pigment as described above, the amount of the extender pigment used is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and further preferably 0.3 to 3 parts by mass, relative to 100 parts by mass of the solid content of the effect pigment dispersant (Y).

[0202] Examples of the organic solvent include: ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester-based solvents such as ethyl acetate, butyl acetate, methyl benzoate, ethyl ethoxypropionate, ethyl propionate, and methyl propionate; alcohol-based solvents such as isopropanol, n-butanol, isobutanol, and 2-ethylhexanol; ether-based solvents such as tetrahydrofuran, dioxane, and dimethoxyethane; glycol ether-based solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; as well as aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, and the like.

[0203] Examples of the rheology control agent other than the cellulose-based rheology control agent (Y2) include polyacrylic acid-based rheology control agents, mineral-based rheology control agents, and polysaccharide-based rheology control agents.

[0204] The method for applying the effect pigment dispersant (Y) can be a coating method commonly used in the art. Examples of such coating methods include coating methods using a brush or an applicator. Among them, a coating method using an applicator is preferred. The applicator is preferably an airless sprayer, an air sprayer, and a rotary atomization electrostatic coater, such as a paint box coater, and is particularly preferably a rotary atomization electrostatic coater. Using such paint and coating methods, an uncured effect coating film with an excellent coating appearance can be formed.

[0205] The effect coating film formed by using the effect pigment dispersant (Y) has a thickness of 0.5 to 1.5 μm based on the cured coating film. When the effect coating film has a thickness of 0.5 to 1.5 μm based on the cured coating film, the resulting multilayer coating film has excellent gloss.

[0206] Step (5)

[0207] The step (5) of the present invention is a step of preheating the uncured base coating film and the uncured effect coating film.

[0208] The preheating temperature is preferably 60° C. to 100° C., more preferably 70° C. to 90° C. The preheating time is preferably 1 to 5 minutes.

[0209] Step (6)

[0210] Step (6) of the present invention is a step of applying a clear coating (Z) on the preheated effect coating film to form an uncured clear coating film.

[0211] Varnish (Z)

[0212] In the present specification, the "clear coating (Z)" refers to a transparent paint for protecting the primer film, the base coating film, and the effect coating film.

[0213] The varnish (Z) used in this step is preferably a paint commonly used in this area, which contains a base resin, a curing agent and a medium comprising water or an organic solvent. Here, the base resin and the curing agent can be known compounds commonly used in this area. The example of the base resin includes carboxylic acrylic resin, epoxy-containing acrylic resin and hydroxyl-containing acrylic resin. The example of the curing agent used includes melamine resin, urea-formaldehyde resin, polyisocyanate compounds and blocked polyisocyanate compounds.

[0214] Examples of the organic solvent include hydrocarbons such as aliphatic hydrocarbons (e.g., hexane and heptane), aromatic hydrocarbons (e.g., xylene and toluene), and alicyclic hydrocarbons; esters such as ethyl acetate and butyl acetate; ethers such as ethylene glycol monomethyl ether; alcohols such as ethanol, propanol, and 2-ethylhexanol; ketones such as methyl ethyl ketone and methyl isobutyl ketone; amides; and other solvents. Examples of organic solvents containing aromatic hydrocarbons include Swasol 310 and Swasol 1000 (produced by Cosmo Oil Co., Ltd., Japan).

[0215] The varnish (Z) used in the method of the present invention may contain, in addition to the above-mentioned components, color pigments, extender pigments, ultraviolet absorbers, defoamers, thickeners, rust preventives, surface conditioners and the like as required.

[0216] Applying the clear coating (Z) having the above structure can form a clear coating film having a sufficient thickness to protect the base coating film and the effect coating film on the basis of the dry coating film, and having excellent surface finish.

[0217] The varnish (Z) can be applied by using conventional coating methods commonly used in the art. The example of the coating method includes a coating method using a brush or an applicator. Wherein, the coating method using an applicator is preferred. For example, the applicator is preferably an airless sprayer, an air sprayer or a rotary atomization electrostatic applicator, such as a paint box applicator, and a particularly preferred rotary atomization electrostatic applicator. The use of the above-mentioned varnish and coating method can form an uncured clear coating film with excellent coating appearance.

[0218] For example, from the viewpoint of obtaining a multilayer coating film having excellent finished appearance and gloss, the clear coating film formed by using the clear coating (Z) has a thickness of preferably 15 to 40 μm, particularly preferably 20 to 30 μm, based on the cured coating film.

[0219] Step (7)

[0220] In step (7) of the present invention, the preheated primer coating film, base coating film, effect coating film and uncured clear coating film are heated in a temperature range of 110° C. to 130° C. to cure these coating films simultaneously.

[0221] The heating can be performed by hot air heating, infrared heating, or high frequency heating. The heating temperature is preferably 110° C. to 130° C. The heating time is preferably 10 to 60 minutes, more preferably 15 to 40 minutes.

[0222] Example

[0223] The present invention is described in more detail below with reference to preparation examples, examples and comparative examples. These preparation examples, examples and comparative examples are only examples and are not intended to limit the scope of the present invention. In the preparation examples, examples and comparative examples, unless otherwise specified, parts and percentages are based on mass. The thickness of the coating film is based on the coating film after it is cured.

[0224] Hydroxyl-containing acrylic resin particles (X1) having a core-shell structure (wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g);

[0225] Preparation Example 1

[0226] 128 parts of deionized water and 2 parts of Adeka Reasoap SR-1025 (trade name, produced by Adeka Corporation, emulsifier, active ingredient: 25%) were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping funnel. The mixture was stirred and mixed in a nitrogen stream and heated to 80°C.

[0227] Subsequently, 1% of the total amount of the monomer emulsion for the core part as shown below and 5.3 parts of 6% ammonium persulfate aqueous solution were added to the reaction vessel and kept at 80°C for 15 minutes. Then the remaining monomer emulsion for the core part was added dropwise to the reaction vessel at the same temperature within 3 hours. After the addition was completed, the mixture was aged for 1 hour. Subsequently, the shell part emulsion as shown below was added dropwise to the reaction vessel within 1 hour, followed by aging for 1 hour. The mixture was then cooled to 30°C, and 40 parts of 5% 2-(dimethylamino)ethanol aqueous solution were gradually added to the reaction vessel, and filtered with 100 mesh nylon cloth, thereby obtaining hydroxyl-containing acrylic resin particles (X1-1) with a core-shell structure having an average particle diameter of 100nm, wherein the acid value of the shell with a solid content of 30% was 90mg KOH / g to 100mg KOH / g. The obtained hydroxyl group-containing acrylic resin particles (X1-1) having a core-shell structure (in which the acid value of the shell was 90 to 100 mg KOH / g) had an acid value of the shell of 96 mg KOH / g.

[0228] Monomer emulsion for core part: 40 parts of deionized water, 2.8 parts of Adeka Reasoap SR-1025, 2.1 parts of methylenebisacrylamide, 22.9 parts of styrene, 25 parts of methyl methacrylate, 15 parts of ethyl acrylate, and 5 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for core part.

[0229] Monomer emulsion for shell portion: 17 parts of deionized water, 1.2 parts of Adeka Reasoap SR-1025, 0.03 parts of ammonium persulfate, 2.8 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 4.4 parts of methacrylic acid, 6 parts of methyl methacrylate, 1.8 parts of ethyl acrylate, and 12.8 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for shell portion.

[0230] Hydroxyl-containing acrylic resin particles (X2) having a core-shell structure (wherein the acid value of the shell is 110 to 120 mg KOH / g) preparation;

[0231] Preparation Example 2

[0232] 128 parts of deionized water and 2 parts of Adeka Reasoap SR-1025 (trade name, produced by Adeka Corporation, emulsifier, active ingredient: 25%) were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping funnel. The mixture was stirred and mixed in a nitrogen stream and heated to 80°C.

[0233] Subsequently, 1% of the total amount of the monomer emulsion for the core part as shown below and 5.3 parts of 6% ammonium persulfate aqueous solution were added to the reaction vessel and kept at 80°C for 15 minutes. Then the remaining monomer emulsion for the core part was added dropwise to the reaction vessel at the same temperature within 3 hours. After the addition was completed, the mixture was aged for 1 hour. Subsequently, the monomer emulsion for the shell part as shown below was added dropwise to the reaction vessel within 1 hour, and then aged for 1 hour. Then, while 40 parts of 5% 2-(dimethylamino)ethanol aqueous solution were gradually added to the reaction vessel, the mixture was cooled to 30°C and filtered with 100 mesh nylon cloth to obtain hydroxyl-containing acrylic resin particles (X2-1) with a core-shell structure having an average particle size of 100nm, wherein the acid value of the shell with a solid content of 30% was 110mg KOH / g to 120mg KOH / g. The obtained hydroxyl group-containing acrylic resin particles (X2-1) having a core-shell structure (in which the acid value of the shell was 110 to 120 mg KOH / g) had an acid value of the shell of 115 mg KOH / g.

[0234] Monomer emulsion for core part: 40 parts of deionized water, 2.8 parts of Adeka Reasoap SR-1025, 2.1 parts of methylenebisacrylamide, 22.9 parts of styrene, 15 parts of methyl methacrylate, 15 parts of ethyl acrylate, and 15 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for core part.

[0235] Monomer emulsion for shell portion: 17 parts of deionized water, 1.2 parts of Adeka Reasoap SR-1025, 0.03 parts of ammonium persulfate, 2.8 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 5.3 parts of methacrylic acid, 10 parts of methyl methacrylate, 3.7 parts of ethyl acrylate, and 6 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for shell layer portion.

[0236] Preparation of another hydroxyl-containing acrylic resin particle (C)

[0237] Preparation Example 3

[0238] 128 parts of deionized water and 2 parts of Adeka Reasoap SR-1025 (trade name, produced by Adeka Corporation, emulsifier, active ingredient: 25%) were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping funnel. The mixture was stirred and mixed in a nitrogen stream and heated to 80°C.

[0239] Subsequently, 1% of the total amount of the monomer emulsion for the core part as shown below and 5.3 parts of 6% ammonium persulfate aqueous solution were added to the reaction vessel and kept at 80°C for 15 minutes. Then the remaining monomer emulsion for the core part was added dropwise to the reaction vessel at the same temperature within 3 hours. After the addition was completed, the mixture was aged for 1 hour. Subsequently, the monomer emulsion for the shell part as shown below was added dropwise to the reaction vessel within 1 hour, followed by aging for 1 hour. The mixture was then cooled to 30°C, and 40 parts of 5% 2-(dimethylamino)ethanol aqueous solution were gradually added to the reaction vessel, and filtered with 100 mesh nylon cloth to obtain hydroxyl-containing acrylic resin particles (C-1) with a core-shell structure having an average particle size of 100nm and a solid content of 30%. The acid value of the shell of the obtained hydroxyl-containing acrylic resin particles (C-1) with a core-shell structure was 85mg KOH / g.

[0240] Monomer emulsion for core part: 40 parts of deionized water, 2.8 parts of Adeka Reasoap SR-1025, 2.1 parts of methylenebisacrylamide, 22.9 parts of styrene, 25 parts of methyl methacrylate, 15 parts of ethyl acrylate, and 5 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for core part.

[0241] Monomer emulsion for shell portion: 17 parts of deionized water, 1.2 parts of Adeka Reasoap SR-1025, 0.03 parts of ammonium persulfate, 3.3 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 3.9 parts of methacrylic acid, 6 parts of methyl methacrylate, 1.8 parts of ethyl acrylate, and 12.8 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for shell portion.

[0242] Preparation Example 4

[0243] 128 parts of deionized water and 2 parts of Adeka Reasoap SR-1025 (trade name, produced by Adeka Corporation, emulsifier, active ingredient: 25%) were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping funnel. The mixture was stirred and mixed in a nitrogen stream and heated to 80°C.

[0244] Subsequently, 1% of the total amount of the monomer emulsion for the core part as shown below and 5.3 parts of 6% ammonium persulfate aqueous solution were added to the reaction vessel and kept at 80°C for 15 minutes. Then the remaining monomer emulsion for the core part was added dropwise to the reaction vessel at the same temperature within 3 hours. After the addition was completed, the mixture was aged for 1 hour. Subsequently, the monomer emulsion for the shell part as shown below was added dropwise to the reaction vessel within 1 hour, followed by aging for 1 hour. The mixture was then cooled to 30°C, and 40 parts of 5% 2-(dimethylamino)ethanol aqueous solution were gradually added to the reaction vessel, and filtered with 100 mesh nylon cloth to obtain hydroxyl-containing acrylic resin particles (C-2) with a core-shell structure having an average particle size of 100nm and a solid content of 30%. The acid value of the shell of the resulting hydroxyl-containing acrylic resin particles (C-2) with a core-shell structure was 106mg KOH / g.

[0245] Monomer emulsion for core part: 40 parts of deionized water, 2.8 parts of Adeka Reasoap SR-1025, 2.1 parts of methylenebisacrylamide, 22.9 parts of styrene, 18 parts of methyl methacrylate, 15 parts of ethyl acrylate, and 12 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for core part.

[0246] Monomer emulsion for shell portion: 17 parts of deionized water, 1.2 parts of Adeka Reasoap SR-1025, 0.03 parts of ammonium persulfate, 3.3 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 4.9 parts of methacrylic acid, 8.8 parts of methyl methacrylate, 1.8 parts of ethyl acrylate, and 9 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for shell portion.

[0247] Preparation Example 5

[0248] 128 parts of deionized water and 2 parts of Adeka Reasoap SR-1025 (trade name, produced by Adeka Corporation, emulsifier, active ingredient: 25%) were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping funnel. The mixture was stirred and mixed in a nitrogen stream and heated to 80°C.

[0249] Subsequently, 1% of the total amount of the monomer emulsion for the core part as shown below and 5.3 parts of 6% ammonium persulfate aqueous solution were added to the reaction vessel and kept at 80°C for 15 minutes. Then the remaining monomer emulsion for the core part was added dropwise to the reaction vessel at the same temperature within 3 hours. After the addition was completed, the mixture was aged for 1 hour. Subsequently, the monomer emulsion for the shell part as shown below was added dropwise to the reaction vessel within 1 hour, followed by aging for 1 hour. The mixture was then cooled to 30°C, and 40 parts of 5% 2-(dimethylamino)ethanol aqueous solution were gradually added to the reaction vessel, and filtered with 100 mesh nylon cloth to obtain hydroxyl-containing acrylic resin particles (C-3) with a core-shell structure having an average particle size of 100nm and a solid content of 30%. The acid value of the shell of the resulting hydroxyl-containing acrylic resin particles (C-3) with a core-shell structure was 126mg KOH / g.

[0250] Monomer emulsion for core part: 40 parts of deionized water, 2.8 parts of Adeka Reasoap SR-1025, 2.1 parts of methylenebisacrylamide, 22.9 parts of styrene, 12 parts of methyl methacrylate, 18 parts of ethyl acrylate, and 12 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for core part.

[0251] Monomer emulsion for shell portion: 17 parts of deionized water, 1.2 parts of Adeka Reasoap SR-1025, 0.03 parts of ammonium persulfate, 2.8 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 5.8 parts of methacrylic acid, 10 parts of methyl methacrylate, 3.2 parts of ethyl acrylate, and 6 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion for shell portion.

[0252] Preparation of hydroxyl-containing acrylic resin solution

[0253] Preparation Example 6

[0254] 35 parts of propylene glycol monopropyl ether were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping funnel, and heated to 85° C. Then, 30 parts of methyl methacrylate, 20 parts of 2-ethylhexyl acrylate, 29 parts of n-butyl acrylate, 15 parts of 2-hydroxyethyl acrylate, 6 parts of

[0255] A mixture of acrylic acid, 15 parts of propylene glycol monopropyl ether and 2.3 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was dripped therein. After completion of the dripping, the resulting mixture was aged for 1 hour. Then, a mixture of 10 parts of propylene glycol monopropyl ether and 1 part of 2,2'-azobis(2,4-dimethylvaleronitrile) was dripped therein within 1 hour. After completion of the dripping, the resulting mixture was aged for 1 hour. 7.4 parts of diethanolamine were added thereto to obtain a hydroxyl-containing acrylic resin solution (R-1) having a solid content of 55%. The acid value of the resulting hydroxyl-containing acrylic resin solution (R-1) was 47 mg KOH / g, the hydroxyl value was 72 mg KOH / g, and the weight-average molecular weight was 58,000.

[0256] Preparation of acrylic resin solution containing hydroxyl and phosphoric acid groups

[0257] Preparation Example 7

[0258] A mixed solvent of 27.5 parts of methoxypropanol and 27.5 parts of isobutyl alcohol was placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet pipe and a dropping device, and heated to 110° C. 121.5 parts of a mixture consisting of 25.0 parts of styrene, 27.5 parts of n-butyl methacrylate, 20.0 parts of “isostearyl acrylate” (trade name, produced by Osaka Organic Chemical Industry Co., Ltd., branched higher alkyl acrylate), 7.5 parts of 4-hydroxybutyl acrylate, 15.0 parts of a polymerizable monomer containing a phosphoric acid group shown below, 12.5 parts of 2-methacryloyloxyethyl acid phosphate, 10.0 parts of isobutyl alcohol and 4.0 parts of tert-butyl peroxyoctanoate was added to the mixed solvent over 4 hours. A mixture consisting of 0.5 parts of tert-butyl peroxyoctanoate and 20.0 parts of isopropyl alcohol was added dropwise over 1 hour. The mixture was then stirred and aged for 1 hour to obtain an acrylic resin solution (R-2) containing hydroxyl groups and phosphoric acid groups having a solid content of 50%. The obtained acrylic resin solution (R-2) containing hydroxyl groups and phosphoric acid groups had an acid value of 83 mg KOH / g, a hydroxyl value of 29 mg KOH / g, and a weight average molecular weight of 10,000.

[0259] Polymerizable monomer containing phosphoric acid group: 57.5 parts of monobutyl phosphate and 41.0 parts of isobutyl alcohol were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet pipe and a dropping device. After the resulting mixture was heated to 90°C, 42.5 parts of glycidyl methacrylate were added dropwise over 2 hours. The resulting mixture was stirred and aged for 1 hour. Then 59.0 parts of isopropyl alcohol were added to obtain a polymerizable monomer solution containing phosphoric acid group with a solid content of 50%. The acid value of the resulting monomer was 285 mg KOH / g.

[0260] Preparation of hydroxyl-containing polyester resin

[0261] Preparation Example 8

[0262] 109 parts of trimethylolpropane, 141 parts of 1,6-hexanediol, 126 parts of 1,2-cyclohexanedicarboxylic anhydride and 120 parts of adipic acid were placed in a reactor equipped with a thermometer, a thermostat, a stirrer, a reflux condenser and a water separator, heated from 160°C to 230°C in 3 hours, and then subjected to condensation reaction at 230°C for 4 hours. Subsequently, 38.3 parts of trimellitic anhydride were added to introduce carboxyl groups into the resulting condensation reaction product, the reaction was carried out at 170°C for 30 minutes, and then diluted with 2-ethyl-1-hexanol to obtain a hydroxyl-containing polyester resin solution (R-3) having a solid content of 70%. The resulting hydroxyl-containing polyester resin solution (R-3) had an acid value of 46 mg KOH / g, a hydroxyl value of 150 mg KOH / g, and a number average molecular weight of 1400.

[0263] Preparation of blocked polyisocyanate compounds

[0264] Preparation Example 9

[0265] 360 parts of "Sumidur N-3300" (trade name, produced by Sumika Bayer Urethane Co., Ltd., Sumidur is a registered trademark, hexamethylene diisocyanate-derived polyisocyanate having an isocyanurate structure, solid content: about 100%, isocyanate group content: 21.8%), 60 parts of "Uniox M-550" (trade name, produced by NOF, Uniox is a registered trademark, polyethylene glycol monomethyl ether, average molecular weight: about 550), and 0.2 parts of 2,6-di-tert-butyl-4-methylphenol were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet pipe, a dropper, and a simple trap for removing the solvent, and mixed thoroughly. The resulting mixture was heated at 130° C. for 3 hours under a nitrogen stream. Subsequently, 110 parts of ethyl acetate and 252 parts of diisopropyl malonate were added. While stirring under a nitrogen stream, 3 parts of a 28% methanol solution of sodium methoxide were added thereto, and the resulting mixture was stirred at 65° C. for 8 hours. The amount of isocyanate in the resulting resin solution was 0.12 mol / kg. 683 parts of 4-methyl-2-pentanol were then added thereto. While maintaining the system temperature at 80 to 85° C., the solvent was evaporated under reduced pressure for 3 hours to obtain 1010 parts of a blocked polyisocyanate compound (R-4). A simple trap for removing the solvent contained 95 parts of isopropanol. The solid content concentration of the blocked polyisocyanate compound (R-4) was about 60%.

[0266] Preparation of Colored Pigment Dispersants

[0267] Preparation Example 10

[0268] 5.5 parts (resin solid content: 3 parts) of the hydroxyl-containing acrylic resin solution (R-1) obtained in Preparation Example 6, 1 part of Carbon MA-100 (trade name, produced by Mitsubishi Chemical Corporation, a carbon black pigment), and 20 parts of deionized water were mixed. After the mixture was adjusted to pH 8.2 with 2-(dimethylamino)ethanol, the mixture was dispersed on a paint shaker for 30 minutes to obtain a colored pigment dispersant (P-1).

[0269] Preparation of Extender Pigment Dispersants

[0270] Preparation Example 11

[0271] 5.5 parts (resin solid content: 3 parts) of the hydroxyl-containing acrylic resin solution (R-1) obtained in Preparation Example 6, 10 parts of Barifine BF-20 (trade name, produced by Sakai Chemical Industry Co., Ltd., a barium sulfate pigment), 0.6 parts (solid content: 0.3 parts) of Surfynol 104A (trade name, produced by Air Products, a defoaming agent, solid content: 50%), and 20 parts of deionized water were mixed. The mixture was dispersed for 1 hour using a paint shaker, thereby obtaining an extender pigment dispersant (P-2).

[0272] Preparation of effect pigment dispersants

[0273] Preparation Example 12

[0274] In a stirring mixer, 8 parts (solid content: 6 parts) of Alpaste TCR2060 (trade name, produced by Toyo Aluminium KK, an aluminum pigment paste, aluminum content: 75%), 35.0 parts of 2-ethyl-1-hexanol, and 8 parts (solid content: 4 parts) of the hydroxyl group- and phosphoric acid group-containing acrylic resin solution (R-2) obtained in Preparation Example 7 were uniformly mixed to obtain an effect pigment dispersant (P-3).

[0275] Preparation of water-based paint (X)

[0276] Preparation Example 13

[0277] 60 parts (solid content: 18 parts) of the hydroxyl-containing acrylic resin particles (X1-1) obtained in Preparation Example 1 (which are resin particles having a core-shell structure, wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g), 40 parts (solid content: 12 parts) of the hydroxyl-containing acrylic resin particles (X2-1) obtained in Preparation Example 2 (which are resin particles having a core-shell structure, wherein the acid value of the shell is 110 mg KOH / g to 120 mg KOH / g) were added. 42.9 parts (solid content: 30 parts) of the polyester resin solution (R-4) obtained in Preparation Example 8, 25 parts (solid content: 15 parts) of the blocked polyisocyanate compound (R-5) obtained in Preparation Example 9, 26.5 parts of the colored pigment dispersant (P-1) obtained in Preparation Example 10, 36.1 parts of the extender pigment dispersant (P-2) obtained in Preparation Example 11, 51 parts of the effect pigment dispersant (P-3) obtained in Preparation Example 12, 21.4 parts (solid content: 15 parts) of melamine resin (weight average molecular weight: 1200, solid content: 70%), and 5.4 parts (solid content: 1.5 parts) of "UH-752" (trade name, produced by Adeka Corporation, associative thickener, solid content: 28%) are uniformly mixed. 2-(Dimethylamino)ethanol and deionized water were added to the mixture to obtain a water-based paint (X-1) having a pH of 8.0, a paint solid content of 25%, and a paint viscosity B6 value of 4000 mPa·s measured at a temperature of 20° C. The B6 value refers to the viscosity measured by a Brookfield viscometer after rotating the rotor at a speed of 6 rpm for 1 minute. As the Brookfield viscometer, a VDA digital viscometer (manufactured by Shibaura System Co., Ltd.) was used.

[0278] Preparation Examples 14 to 20

[0279] Water-based paints (X-2) to (X-8) having a pH value of 8.0 were obtained in the same manner as in Preparation Example 13, except that the formulations and viscosities were as shown in Table 1. The amounts of the components shown in Table 1 are based on mass solid content.

[0280] Table 1

[0281]

[0282]

[0283] (*1) "primal ASE-60" (trade name, produced by Dow Chemical Company, alkaline swelling thickener, solid content: 28%).

[0284] Preparation of effect pigment dispersant (Y)

[0285] Preparation Example 21

[0286] In a stirred mixing container, an acetylene glycol-based surface conditioner (solid content: 0.3 parts), Alpaste EMR-B6360 (trade name, non-leafing aluminum flakes, produced by Toyo Aluminium KK, average particle size D50: 10.3 μm, average thickness: 0.19 μm, surface treated with silica) (solid content: 1.5 parts), a phosphoric acid group-containing cellulose nanofiber aqueous dispersant (number average fiber diameter: 4 nm, phosphoric acid group introduction amount: 1.50 mmol / g) (solid content: 0.5 parts), a triazine-based ultraviolet absorber (solid content 0.1 parts), a hindered amine-based light stabilizer (solid content: 0.1 parts), and the color pigment dispersant (P-1) obtained in Preparation Example 10 (solid content: 0.1 parts) were stirred and mixed. Subsequently, a liquid mixture of water and isopropyl alcohol (water / isopropyl alcohol = 6 / 1) was added to prepare an effect pigment dispersant (Y-1) having a solid content of 4.5%. The coating viscosity B6 value is 1500 mPa·s.

[0287] Preparation of water-based primer (W)

[0288] Water-based primer (W-1): Ascalex 2870CD-1 Dark Gray (trade name, produced by Kansai Paint Co., Ltd., an acrylic resin-based water-based conductive primer for PP materials) was used as the water-based primer (W-1).

[0289] Preparation of varnish (Z)

[0290] Clear varnish (Z-1): KINO6510 (trade name, produced by Kansai Paint Co., Ltd., a hydroxyl / isocyanate-curable, acrylic resin / urethane resin-based two-component organic solvent-based paint) was used as the clear varnish (Z-1).

[0291] Preparation of test substrates

[0292] Black polypropylene plastic molded articles were degreased to prepare the test substrates.

[0293] Preparation of coating test panels

[0294] Example 1

[0295] The water-based primer (W-1) was coated on the test substrate using a rotary atomizing coater to a cured film thickness of 9 μm to form an uncured base coating film. The coated substrate was allowed to stand for 3 minutes and then preheated at 60° C. for 3 minutes.

[0296] Subsequently, under the conditions of a booth temperature of 22° C. and a humidity of 78%, the water-based base paint (X-1) obtained in Preparation Example 13 was applied to the preheated base coating film using Robot Bell (manufactured by ABB) to a film thickness of 10 μm based on the dry coating film, thereby forming an uncured base coating film. The resulting product was allowed to stand for 3 minutes.

[0297] Subsequently, under the conditions of a booth temperature of 22° C. and a humidity of 78%, the effect pigment dispersant (Y-1) obtained in Preparation Example 21 was applied to the uncured base coating film using Robot Bell (manufactured by ABB) to a film thickness of 0.6 μm based on the dry coating film, thereby forming an effect coating film. The resulting product was allowed to stand for 3 minutes and then preheated at 80° C. for 3 minutes.

[0298] Then, under the conditions of booth temperature of 23° C. and humidity of 68%, the clear coating (Z-1) was applied to the preheated (uncured) effect coating using Robot Bell (manufactured by ABB) to form a clear coating having a film thickness of 25 μm based on the dry coating. After the coating was completed, the resulting product was allowed to stand at room temperature for 7 minutes, and then heated at 120° C. for 30 minutes in a hot air circulation drying oven while drying the multilayer coating to obtain a test plate.

[0299] Example 2 and Comparative Examples 1 to 6

[0300] A test plate was obtained in the same manner as in Example 1, except that the paint used was as shown in Table 2.

[0301] Coating evaluation

[0302] The test plates obtained in the above manner were evaluated based on the following criteria. Table 2 shows the results.

[0303] 60 degree mirror gloss (60 degree gloss)

[0304] Use a multi-angle spectrophotometer to measure the L* value (L*15 value) of each test plate at an incident angle of 15°. The higher the value, the better. 178 points and above are considered passed.

[0305] Finished product appearance: drooping

[0306] Each test panel was visually observed and the degree of occurrence of sagging was evaluated according to the following criteria: Pass: No sagging was observed and the coating film appearance was excellent.

[0307] Fail: Sagging is observed and the film appearance is inadequate.

[0308] Finished product appearance: smoothness

[0309] Each test panel was visually inspected and the finish was evaluated according to the following criteria.

[0310] Pass: Excellent finish and excellent coating film appearance.

[0311] Fail: The finish is poor and the film appearance is inadequate.

[0312] Table 2

[0313]

Claims

1. A method for forming a multilayer coating film, comprising the following steps in sequence: Step (1): applying a water-based primer (W) on a plastic molded product to form an uncured primer film; Step (2): preheating the uncured primer film; Step (3): applying a water-based base paint (X) on the preheated base coating film to form an uncured base coating film; Step (4): applying an effect pigment dispersant (Y) on the uncured base coating film to form an uncured effect coating film; Step (5): preheating the uncured base coating film and the uncured effect coating film; Step (6): applying a clear coating (Z) on the preheated effect coating film to form an uncured clear coating film; as well as Step (7): heating the preheated primer film, the preheated base film, the preheated effect film and the uncured clear film at a temperature ranging from 110° C. to 130° C. to simultaneously cure the films, wherein The water-based paint (X) comprises Hydroxyl-containing acrylic resin particles (X1) having a core-shell structure, wherein the acid value of the shell is 90 mg KOH / g to 100 mg KOH / g; Hydroxyl-containing acrylic resin particles (X2) having a core-shell structure, wherein the acid value of the shell is 110 to 120 mgKOH / g; and Associative thickener (X3); The mass ratio (X1 / X2) of the hydroxyl-containing acrylic resin particles (X1) to the hydroxyl-containing acrylic resin particles (X2) contained in the water-based paint is 70 / 30 to 30 / 70; The effect pigment dispersant (Y) comprises Flake aluminum pigment (Y1), Cellulose-based rheology control agent (Y2), a surface conditioner (Y3), and water, and The effect pigment dispersant (Y) has a solid content of 2% by mass to 6% by mass; and The effect coating film after curing has a film thickness of 0.5 μm to 1.5 μm.

Citation Information

Patent Citations

  • Method for forming multi-layer coating film

    WO2018092874A1